Deep electrical structure over the igneous arc of the Indo Burman Orogen in Sagaing province, Myanmar from magnetotelluric studies - Rao, C. K.; Selvaraj, C.; Gokarn, S. G. (My University, 2014)
Magnetotelluric studies over the igneous arc of the Indo Burman range in the Sagaing province of Myanmar have delineated the high resistivity Indian plate subducting westwards beneath the Burmese block to depths of 30 km and beyond. The thick moderately resistive (20–100 Ω m) layer overlying the subducting Indian plate may be due to the low resistivity sediments. The entire region is covered with prominent sedimentary layer with a conductance varying between 20 and 3000 S showing a general increase from the east to west, suggesting that their thickness increases toward the west. The large unsystematic variations in the conductance are indicative of the widely varying depositional environments and also possible vertical block movements during the course of their deposition. A west dipping low resistivity zone to the east of Burmese block seems to demarcate its eastern limit, suggesting the possibility of a hitherto unknown deep seated fault, which is also supported by the several earthquake foci located over this zone. The nature of the crustal movements over this fault is not immediately apparent. Possibility exists that the Sagaing fault is an en echelon fault and the present feature observed here is a part of this en echelon fault. The possibility of channel flows of the weakened rocks in the deep crust observed in the vicinity of the eastern Himalayan syntaxis may also cause such low resistivity zones.
Keywords: Indo burman orogen; Magnetotellurics; Indo Myanmar suture